2017
DOI: 10.1108/md-07-2016-0464
|View full text |Cite
|
Sign up to set email alerts
|

Proactive personality, core self-evaluations, and engagement: the role of negative emotions

Abstract: Purpose The authors examined the simultaneous indirect effects of proactive personality (PP) and core self-evaluations (CSEs) on the work outcomes of employee task performance and affective organizational commitment (AOC) via job engagement. Additionally, the authors tested the potential energizing capacity of high negative work affect in this process. The paper aims to discuss these issues. Design/methodology/approach Data were collected from a sample of teachers in the South-Eastern USA (n=193). The online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
(66 reference statements)
0
16
0
4
Order By: Relevance
“…The JES is a three-factor scale (cognitive, emotional, and physical engagement) with separate six scales for each factor. This measure is widely used in the engagement literature (Rich et al, 2010;Shuck and Reio, 2014;Haynie et al, 2017). Internal consistency reliability estimates for each subscale in the current study was as follows: cognitive engagement, = 0.89 (six items); emotional engagement, = 0.91 (six items); physical engagement, = 0.853 (six items).…”
Section: A Eementioning
confidence: 70%
“…The JES is a three-factor scale (cognitive, emotional, and physical engagement) with separate six scales for each factor. This measure is widely used in the engagement literature (Rich et al, 2010;Shuck and Reio, 2014;Haynie et al, 2017). Internal consistency reliability estimates for each subscale in the current study was as follows: cognitive engagement, = 0.89 (six items); emotional engagement, = 0.91 (six items); physical engagement, = 0.853 (six items).…”
Section: A Eementioning
confidence: 70%
“…Consistent with this perspective, several studies have demonstrated that proactive personality may influence work outcomes via its effects on one's sense of work involvement and engagement (e.g., Bakker, Tims, & Derks, 2012;Haynie, Flynn, & Mauldin, 2017;Wang, Zhang, Thomas, Yu, & Spitzmueller, 2017). Indeed, Joo and Kim (2009) report that proactive personality shapes intrinsic motivation partly via greater perceptions of job complexity.…”
Section: Intrinsic Motivationmentioning
confidence: 93%
“…En primer lugar, puesto que las CSE representan la base desde la cual los individuos perciben y experimentan los diferentes dominios de sus vidas, incluido el laboral, se espera que niveles mayores de CSE tiendan a conducir a actitudes más positivas hacia el trabajo (Wu y Griffin, 2012), como el work engagement (Tims y Akkermans, 2017). En segundo lugar, los individuos con CSE más positivas suelen focalizarse en los aspectos más favorables de sus tareas (Kammeyer-Mueller et al, 2009), observar mayor compromiso con su trabajo (Peng et al, 2016) e invertir mayor energía emocional y cognitiva en el mismo (Zhang et al, 2014), lo que se encuentra asociado con mayores niveles de motivación intrínseca y work engagement (Chang et al, 2012;Albrecht, 2010;Bakker, 2011;Haynie et al, 2017). En tercer lugar, los individuos con CSE más positivas son más proclives a perseguir metas que resulten más coincidentes con sus valores, intereses y objetivos personales , encontrándose más intrínsecamente motivados a alcanzarlas y experimentando, como resultado, mayores niveles de work engagement (Van Doorn y Hulsheger, 2015; Ferris et al, 2011;Albrecht, 2010).…”
Section: Las Autoevaluaciones Esenciales Y El Work Engagementunclassified
“…En este sentido, la evidencia señala que los individuos con mayores CSE suelen percibir y experimentar las características de su trabajo de manera más positiva (Tims y Akkermans, 2017), focalizarse en los aspectos más favorables de sus tareas (Kammeyer-Mueller, Judge y Scott, 2009) y perseguir metas más coincidentes con sus valores, intereses y objetivos personales (Judge, Bono, Erez y Locke, 2005). Como resultado, estos individuos tienden a invertir más energía emocional y cognitiva en su trabajo (Peng, Li, Zhang, Tian, Miao, Xiao y Zhang, 2016;Zhang, Wu, Miao, Yan y Peng, 2014) y a experimentar mayor motivación intrínseca durante el ejercicio de su rol (van Doorn y Hulsheger, 2015; Ferris, Rosen, Johnson, Brown, Risavy y Heller, 2011), fenómenos que suelen conducir a mayores niveles de work engagement (Chang, Ferris, Johnson, Rosen y Tan, 2012;Bakker, 2011;Haynie, Flynn y Mauldin, 2017).…”
Section: Introductionunclassified